Language Retention and Attitudes Among Foreign Students in Learning Mandarin at Jinan University: Sociolinguistic Studies - Sheyra Silvia Siregar; Sheyla Silvia Siregar; Juni Dwi Alvionita Pinem; Umi Hanifah Zahra Ghazaly (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2023)
This research is entitled "Language Retention and Attitudes Among Foreign Students in Learning Mandarin at Jinan University: Sociolinguistic Studies". The purpose of this study is to describe language retention and attitudes among foreign students in learning Mandarin at Jinan University: a bilingual context. The method used to analyze is a quantitative approach to describe the maintenance of the mother tongue in learning Mandarin by foreign students at Jinan University. In this study, two variables were used, namely the dependent variable and the independent variable. The method used in collecting data is a questionnaire method with interviews. Data obtained by distributing questionnaires to respondents. The research data assessment method uses a qualitative method with the generation of a sample of the population. Data were analyzed by applied sociolinguistic theory by J.A.Fishman